Universalitas Islam dalam Peace Education: Meretas Jalan Menuju Masyarakat Multikultural yang Harmonis - Fitroturohmawati; Bawon; Sutomo (Journal of Literature Review, 2025)
This article discusses the role of the universality of Islamic values in peace education as a foundation for building a harmonious multicultural society. A descriptive method is used in this study to describe and analyze in depth how universal Islamic values can be integrated into peace education to pave the way towards a harmonious multicultural society. This approach aims to provide a comprehensive understanding of Islam's contribution to creating a culture of peace through principles such as justice, compassion, tolerance, and respect for diversity. By reviewing literature on the foundations of universal Islamic values, peace education, and the social challenges that arise in a multicultural context, the descriptive method allows for a systematic exploration of the various dynamics that influence the effectiveness of peace education based on Islamic values. The universality of Islam, reflected in the principles of justice, compassion, tolerance, and respect for diversity, serves as an important foundation for instilling mutual respect and managing differences constructively. In its implementation, Islam-based peace education faces various challenges, such as misunderstandings of Islam, social conflict due to plurality, curriculum limitations, a lack of multicultural competence among teachers, and minimal community collaboration. To address these challenges, solutions offered include strengthening inclusive curricula, teacher training, participatory learning methods, inter-institutional collaboration, technology utilization, and continuous evaluation. By integrating universal Islamic values into peace education, it is hoped that an inclusive, tolerant, and harmonious society will emerge amidst diversity.